Comparative Effects of Zinc Methionylglycinate and Zine sulfate on Hair coat characteristics and zinc concentration in plasma, hair, and feces of dogs - Thanisara Preedapattarapong (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2007